De novo gain‐of‐function variants in KCNT2 as a novel cause of developmental and epileptic encephalopathy. Issue 6 (27th July 2018) - Ambrosino, Paolo; Soldovieri, Maria Virginia; Bast, Thomas; Turnpenny, Peter D.; Uhrig, Sabine; Biskup, Saskia; Döcker, Miriam; Fleck, Thilo; Mosca, Ilaria; Manocchio, Laura; Iraci, Nunzio; Taglialatela, Maurizio; et al.
Abstract : Variants in several potassium channel genes have been found in developmental and epileptic encephalopathies (DEE). We report on 2 females with de novo variants in KCNT2 with West syndrome followed by Lennox‐Gastaut syndrome or with DEE with migrating focal seizures. After in vitro analysis suggested quinidine‐responsive gain‐of‐function effects, we treated 1 of the girls with quinidine add‐on therapy and achieved marked clinical improvements. This suggests that the new spectrum of KCNT2 ‐related disorders do not only share similar phenotypic and in vitro functional and pharmacological features with previously known KCNT1 ‐related disorders, but also represents a further example for possible precision medicine approaches. Ann Neurol 2018;83:1198–1204